Market reaction to tender and private offers on the JSE - N. Wesson; C. Muller; M. Ward (South African Journal of Business Management, 2017)
Investors can benefit when incorporating the information-signalling effect of share repurchases in their investment strategies. Previous South African studies on open market share repurchases confirmed the globally observed signalling-effect, but found open market share repurchases not to be the outright favoured share repurchase type in this country – as is the case globally. The present study is the first to examine the market reaction to the preferred share repurchase type, namely specific (or tender and private offers) share repurchases, in the South African regulatory environment. Abnormal returns were calculated using a 12-parameter benchmark over a four-year event window, for share repurchases announced from 1999 to 2009. Pro rata tender offers were found not to possess information-signalling benefits, but significant excess returns subsequent to the announcement date were reported for the two private offer types (namely other specific offers and the repurchase by the holding company of shares held by subsidiaries). The other specific offers were found to possess significant information-signalling benefits – especially over the long term and in respect of value companies.
Keywords: 650